Which Retail Firm Characteristics Impact On Financial Distress? - Elok Heniwati; Erlina Essen (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study is to examine whether liquidity, profitability, leverage, sales growth, operating capacity, and size have influenced on financial distress by using retail industry that listed in the Indonesia Capital Market. Sample determination basing on purposive sampling results 19 companies with complete data over the observation period (2014-2018). Data was manually collected from the website, www.idx.com. By using logistic regression, the findings show that profitability and leverage have significant influenced on financial distress. Moreover, predictor liquidity, sales growth, operating capacityand firm’s size have no relationship with financial distress.